Double Binds and (Re)Imagined Storylines: Las Obligaciones of Being a Latina Teacher in a New Latinx Community. Issue 3 (3rd July 2019) - Colomer, Soria
Abstract : Latinx teachers have been positioned as both role models and agents of change in schooling communities that are often racially contentious. As members of both the Latinx community and the school community, Latinx teachers have the agency to (re)define storylines by either submitting to or resisting positioning acts. Storylines discussed in this article may mirror the circumstances in which many Latinx teachers find themselves when they face a systemic double bind—a commitment to their Latinx community while employed in a culturally subtractive context regulated by restrictive accountability policies. This article reveals how teachers, school administrators, and teacher educators might (re)position both Latinx teachers and themselves to (re)imagine the roles of Latinx teachers in new Latinx communities.